Concept of Economic Crime - Gavelis, Vytautas; Čepas, Algimantas (Ekonomika, 2002)
Economic crime is a selfish continuing act or ommission in the sphere of economic bussiness, committed by owners, directors of bussiness enterprises, their representatives, public officials, which infringe upon state, private bussiness or consumers economic interests. Criteria of economic crime is economic relations, that arise in the sphere of economic bussiness, the participants of which takes rational decisions, and labour, production and financial capital, natural resources are used to create goods and services. Features of economic crime are: 1. Committed in the sphere of economic bussiness. 2. Infringes upon state’s, private bussiness’, consumers’ economic interests. 3. Selfish motives. 4. Continuing character. 5. Committed by owners and directors of private enterprises or their representatives or by public officials that abuse their power. Corruption is an economic crime because of economic nature of it.One of the major factors that influence economic crime is corruptive activities of state officials. Corrupt relations emerge when a state official turns its functions into a good and try to sell the good in a way that contradicts interests of the state, private business or consumers, i.e. become an illegal participant of the economic business. Therefore most of the crimes against the public service due to theirs corruptive nature are to be considered as economic crimes.Economic crime often is of transnational nature and international control of economic crime is necessary. Effective system of it has not come into being yet. The opportunities for extradition in cases of economic crime are not exhausted fully. One of the factors for such a situation - incorrect understanding of the double criminality rule. It should be understood with the help of in abstracto model. Opportunities to apply analogy should be recognized also.